Rancang Bangun Aplikasi Penentuan Harga Pokok Produksi Dengan Metode Job Order Costing (Studi Kasus CV. Rahayu Sentosa Sidoarjo) - Muhammad Abrar; Mochammad Arifin; Vivine Nurcahyawati (Jurnal Sistem Informasi Universitas Dinamika, 2018)
CV. Rahayu Sentosa established in 2012 and during the four years of existence, the company is engaged in the manufacture of customer orders emphasized on making the mold as well as some support work that is precision parts, construction and manufacturing. Starting from just a machine Cutting & Bending plate, now the company has grown and has several machines include CNC machining centers, EDM, turning, and milling.Problems on the CV. Rahayu Sentosa today is there are still some deficiencies in calculating the cost of production of the mold in any orders from consumers so they can not produce a definite price to determine the price of finished goods and how costs are used by the company in making the product. In determining the prices of goods produced, the process of determining the prices of goods are still based on estimates and view pricing of goods by companies engaged in the same field. Whereas goods produced by CV. Rahayu Sentosa are goods that are produced with the accuracy of modern machines and has a precision specifications and adequate quality. On the other hand in calculating the cost of production should be charged the cost of materials, labor costs and factory overhead costsThis resulted in the selling price charged to consumers are not in accordance with the price expected by the company. So that the company's profit in the year 2014-2015 experiencing instability with a decrease in profit of thirty per cent in the manufacturing mold. On the other hand, failure to achieve the company target due to the age of the firm of less than five years, requires the company to frequently hold exhibitions about the company's products outside of the city to be recognized by consumers. This has an impact on the mobility of the company to be able to do pricing quickly and precisely. Based on these problems, the authors make the application of determining the cost of production by using web-based job order costing. Determining the cost of a web-based production can solve the problems on the company today among other things, determine the selling price of goods customers, facilitate the calculation of the cost of production of goods customers by engineering the company's current enterprise mobility is high, as well as enable customers to order goods with web-based applications.